The relationship between work-family conflict and missed nursing care; a cross-sectional study in Iran - Mohammad Javad Ahmadzadeh-Zeidi; Zahra Rooddehghan; Shima Haghani (BMC Nursing)
Abstract Background & aims Work–family conflict, an important issue in nursing management, has been examined extensively worldwide among nurses. Nurses’ inability to handle these conflicts affect their quality of care and may lead to missed nursing care. This study aimed to investigate the relationship between work-family conflict and missed nursing care in Iran. Materials & methods This cross-sectional descriptive-analytical study was conducted on 270 nurses working in two hospitals affiliated to Tehran University of Medical Sciences (Sina & Shariati) from September to December 2023. The research community included all nurses working in medical-surgical wards in the designated hospitals. The research samples were included in the study in a targeted and quota sampling after obtaining organizational permits, ethical approval and informed consent. Data collection was done using three questionnaires including: Demographic information form, Carlson’s work-family conflict and Kalisch MISSCARE Questionnaire. The collected data was analyzed in SPSS software, version 25. Results The results of Pearson’s correlation test showed that there is a positive relationship between nurses’ work-family conflict and missed nursing care scores (r = 0.21) (p = 0.001). The mean (SD) score of nurses’ work-family conflict was reported at a moderate level (61.58(11.57)) and the mean (SD) score of missed nursing care was reported at a low level (47.84(16.48)). Nurses under 29 years old and male nurses had more missed nursing care other than their participants. No more relationship was observed between other demographic variables with missed nursing care and nurses’ work-family conflict. Conclusion According to the results of this research, it can be concluded that the existence of work-family conflict can be an obstacle for the correct implementation of nursing care. In such a way that nurses exposed to higher work-family conflict level had higher missed nursing care. Based on the findings of this research, it is recommended for health care providers and nursing managers to identify nurses exposed to high work-family conflicts, adopt programs to decrease their conflicts and consequently reduce missed nursing care.